Pemodelan dan Evaluasi Proses Bisnis Menggunakan Business Process Model and Notation (BPMN) (Studi Kasus: Percetakan Mabes Printing) - Ghasa Amalul 'Alam; Ismiarta Aknuranda; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mabes Printing is a printer that focuses on digital and offset printing. The Vision of Mabes Printing is to become a printing trusted by customers and provide mutual prosperity for the people who work in it. In carrying out its business processes, Mabes Printing experiences problems in the production business process. The printing process is one of the main processes for Mabes Printing. If the problem in the business process is not immediately addressed, it will pose a great danger to Mabes Printing. In order to find out about the problem, Mabes Printing need a model. Business process model is needed so Mabes Printing can understand the current business process easily. Business process modeling using Business Process Model and Notation (BPMN). After modeling using BPMN, mapping will be done with the problem information. After the problem is found the next step is to find the root causes using 5 Why Analysis. The results of this study are found 4 root problems in the business process of ordering, purchasing raw materials, manufacturing goods and taking goods. The root of the problem in the ordering business process is the lack of design choices given to customers. The root of the problem in the business process of purchasing raw materials is the lack of fast and easy data collection on the raw materials needed for the production carried out. The root of the problem in the business process of manufacturing goods is the absence of rapid and easy data collection to be given to production employees. The root of the problem in the business process of taking goods is that there is no easier way to find customer order data.